P13 Interferon-gamma release assay (IGRA) conversion, reversion and implications for the diagnosis of latent tuberculosis infection using a multimodality approach: a retrospective, observational study within a central London TB centre. (2nd December 2011) - Almond, M H; O'Donoghue, M; Drey, N; Seneviratne, S; Lalvani, A; Wickremasinghe, M; Kon, O M
Abstract : Introduction and Objectives: Accurate diagnosis & management of latent tuberculosis infection (LTBI) among TB contacts is critical for both the health of infected individuals and prevention of disease transmission. Interferon gamma release assays (IGRAs) measure T cell release of interferon-gamma following stimulation by antigens not confounded by the BCG vaccination. The current NICE guidelines recommend their use following a positive TST. In addition some centres have moved to a single step IGRA test for LTBI. Our institution adopts a triple investigation approach comprising a chest radiograph (CXR), TST and IGRA on presentation followed by a rescreen if the TST & IGRA are discordant or if pulmonary contacts are screened prior to 6 weeks. The aim of our study was to evaluate the prevalence of IGRA conversion and reversion in rescreened asymptomatic TB contacts that attended our centre. Methods: This was a retrospective, observational study carried out at a central London teaching hospital. The study population comprised 593 consecutive, adult TB contacts screened between 1 January 2008 and 31 December 2010. Data were collected through retrospective review of chest radiographs, TST & IGRA tests. Results: Of 498 asymptomatic TB contacts screened, 460 had both an initial TST and IGRA performed (Abstract P13 figure 1 ). 81 (17.7%) contacts had discordant TST & IGRA results. 52 (64%) of these discordant cases had a positive TST & Negative IGRA; these patients would have been discharged under NICE guidelines however, our rescreen revealed 9 (17%) positive 2 nd IGRAs that is, conversion. Three of these patients were under 35 and would therefore by eligible for chemoprophylaxis. Twenty-nine (36%) of the discordant cases had a negative TST and positive IGRA however, 8 (28%) of these IGRAs reverted to negative. It is important to note that if following a single-step IGRA screening protocol (ie, without a rescreen) these cases may have been commenced on chemoprophylaxis unnecessarily (four of these reversion cases were under the age of 35). Conclusions: Our results show that adoption of either a sequential TST + ve/IGRA approach or single IGRA approach can result in a significant number of false negative LTBI diagnoses due to IGRA conversion. Conversely, we have also shown that an IGRA rescreen because of discordant TST/IGRA tests can improve LTBI diagnostic specificity and therefore reduce unnecessary chemoprophylaxis due to the effect of reversion.